Antibacterial mechanisms of magnolol against Streptococcus agalactiae and immunomodulatory effects in Schizothorax prenanti - Yilin Wang; Kun Peng; Longjun Deng; Yihao Wang; Qibin Jiang; Tiancai Li; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2026)

Myostatin in fish: current understanding of its characterization, function, and signaling pathways - Yujun Wang; Longjun Deng; Tiancai Li; Li Liu; Dongjie Wang; Wei Luo; Zongjun Du (Fish Physiology and Biochemistry, 2026)

The increasing impact of vegetation productivity on global wetland methane emissions - Longjun Wang; Peng Li; Qiuan Zhu; Xiaolu Zhou; Zhengmiao Deng; Zelin Liu; Ziying Zou; Changhui Peng (Global and Planetary Change, 2026)

Life-cycle regulation of carbohydrate metabolism revealed by glucokinase (gck) in two cyprinids, Spinibarbus denticulatus and Schizothorax prenanti - Yongyao Guo; Yue Zhang; Tiancai Li; Longjun Deng; Zhonggang Guo; Li Liu; Pengyu Chen; Luojia Li; Wei Luo; Dongjie Wang; Zongjun Du (Aquaculture, 2026)

Ammonia nitrogen accumulation and metabolic regulation in large-scale loach (Paramisgurnus dabryanus) exposed to sub-chronic carbonate alkalinity: Insights from biochemical and omics analyses - Wei Luo; Luojia Li; Li Liu; Yujun Wang; Longjun Deng; Tiancai Li; Dongjie Wang; Zongjun Du (Aquaculture, 2026)

Study on the Bioavailability of Arsenic in the Rice–Crayfish Farming System - Kelei Zhang; Shoudong Zhang; Longjun Deng; Tiancai Li; Li Liu; Wei Luo; Yibo Zhang; Yongyao Guo; Dan Liu; Shiyong Yang; Jun Wang; Dongjie Wang; et al. (Fishes, 2025)
Rice–fishery integrated farming has expanded rapidly in China, yet its implications for arsenic (As) accumulation remain insufficiently understood. This study evaluated As bioavailability and enrichment in a rice–crayfish farming system (RCFS) by establishing controlled field plots with soil As concentrations ranging from 5 to 40 mg/kg under three water-management regimes: alternating wetting and drying (AWD), continuously flooded (CF), and RCFS. Soil–water physicochemical variables and As accumulation in both rice organs and crayfish tissues were systematically analyzed, followed by human health risk assessment. Inorganic As in brown rice increased linearly with soil As, following Y = 0.0117X + 0.0598 (R2 = 0.96), and the estimated soil safety thresholds were 26.48 mg/kg for AWD, 11.98 mg/kg for RCFS, and 9.24 mg/kg for CF. AWD consistently exhibited the lowest As risk due to its ability to elevate soil Eh and maintain a more favorable pH, thereby suppressing As mobilization. Compared with CF, RCFS reduced As bioavailability through crayfish-induced bioturbation, which increased Eh, enhanced SOM and CEC, and improved soil aeration. As accumulation in crayfish tissues also rose with soil As, with abdominal muscle As fitting Y = 0.0085X + 0.0553 (R2 = 0.8588). Although abdominal muscle met safety limits, the hepatopancreas accumulated substantially higher As and exceeded carcinogenic risk thresholds, even at 5 mg/kg of soil As, indicating a potential health concern for consumers. This work elucidates As dynamics and enrichment mechanisms in RCFS, providing guidance for safer rice–crayfish production in As-impacted areas.

A comprehensive understanding of thermal tolerance in Percocypris pingi (Tchang, 1930) under different acclimation temperatures supported by behavioral assessments - Yongyao Guo; Tong Li; Li Liu; Tiancai Li; Longjun Deng; Siyi Zhu; Shun Zhong; Qingjie Wang; Dongjie Wang; Wei Luo; Zongjun Du (Journal of Thermal Biology, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

Genotype diversity and antibiotic resistance risk in Aeromonas hydrophila in Sichuan, China - Kun Peng; Mengzhu Chen; Yilin Wang; Ziqi Tian; Longjun Deng; Tiancai Li; Yang Feng; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Brazilian Journal of Microbiology, 2024)

Gill structure and respiratory ability of Euchiloglanis kishinouyei (Osteichthyes: Siluriformes: Sisoridae) - Luojia Li; Longjun Deng; Jie Li; Tiancai Li; Pengyu Chen; Wei Luo; Zongjun Du (Journal of Fish Biology, 2023)
Glyptosternoid fishes are distributed in the torrent environment of alpine canyons, where they often leave the water to climb rocky cliffs. As one of the most primitive species of glyptosternoid fishes, Euchiloglanis kishinouyei was examined in the current study to analyse its gill microstructure and respiratory ability. We first found that the oxygen consumption rate was relatively high and negatively correlated with body mass and that the average oxygen consumption at night was higher than during the day. The asphyxiation point of E. kishinouyei (5.05 ± 0.22 g) was c . 1.93 mg/L. Subsequently, the surface morphology, gross gill tissue structure, and ultra‐microstructure of gill lamellae were investigated using optical microscopy and SEM. The gills showed an overall trend of regression, with five pairs of gill arches in each gill cavity. The adjacent gill filaments had large gaps, and the gill lamellae were thick. The gill filaments were closely arranged on the gill arches, their folded respiratory surface was highly vascularized with no tiny crest, and there were obvious tiny crests, grooves, pits, and pores on the nonrespiratory surface. The gill lamellae were closely embedded on both sides of gill filaments, which were composed of flat epithelial cells, basement membrane, pillar cells, and mucous cells. The gill total respiratory area correlated positively with body mass and length, whereas the gill relative respiratory area correlated negatively with body mass. We comprehensively analysed the gill microstructure and respiratory capacity of E. kishinouyei to provide fundamental data for the adaptive evolution of the gill structures of bimodally respiring fishes and offer insights into further study on the accessory air‐breathing function of skin.

High resistance to Ichthyophthirius multifiliis in Percocypris pingi, an endemic fish in upper Yangtze River - Linzhu Li; Maohua Li; Rukui Zeng; Longjun Deng; Kun Yang; Zhaobin Song (Aquaculture, 2023)

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

Otolith fluorescent and thermal marking of elongate loach (Leptobotia elongata) at early life stages - Kun Yang; Rukui Zeng; Weixiong Gan; Longjun Deng; Zhaobin Song (Environmental Biology of Fishes, 2016)